PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH YANG TERDAFTAR DI BEI TAHUN 2013-2015 - Faradina, Lisca (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
ThisÂ study examinesÂ the influence of the disclosure of intellectual capital on the financial performance of Islamic Banks listed in the Indonesia Stock Exchange in the period of 2013-2015. In this study, there are two variables involved, namely independent variable and dependent variable. The independent variable consists of the company's financial performance, which are Return on Assets (ROA) and Return on Equity (ROE). Meanwhile, the dependent variable used in this research is the intellectual capital that is based on the calculation of Value Added Intellectual Capital (VAICTM). The data analysis was conducted through simple regression method. The results of the data analysis show that intellectual capital increases the financial performance of Islamic Banks, which is in the form of Return on Assets (ROA) and Return on Equity (ROE).Keywords: Intellectual Capital (VAICTM), Return on Assets (ROA), Return on Equity (ROE)